(untitled) (Texas Journal of Medical Science, 2025)
Hypoparathyroidism (HPT) is a rare endocrine disorder characterized by chronic parathyroid hormone (PTH) deficiency, resulting in persistent hypocalcemia, hyperphosphatemia, and reduced calcitriol synthesis. These biochemical abnormalities have a profound impact on renal morphology and function. Numerous studies indicate that long-standing HPT predisposes patients to nephrocalcinosis, nephrolithiasis, tubular injury, interstitial fibrosis, and a progressive decline in glomerular filtration rate. Despite increasing recognition of renal involvement, comprehensive evaluation of morpho-functional kidney changes in HPT remains limited